2020
DOI: 10.1002/app.49403
|View full text |Cite
|
Sign up to set email alerts
|

β‐Polymorph enhancement in poly(vinylidene fluoride) by blending with polyamide 6 and barium titanate nanoparticles

Abstract: Polyamide 6 (PA6) as a cost‐effective polar polymer and barium titanate (BT) as piezoelectric ceramic nanofiller were melt compounded with poly(vinylidene fluoride) (PVDF) matrix to enhance the β electroactive phase. A series of samples with two blending ratios of PVDF/PA6 (90/10 and 70/30 [wt%/wt%]) each containing 1, 3, and 5 wt% of BT were prepared. The SEM results revealed that the addition of BT to the neat blends refined the biphasic morphology which is mainly due to selective localization of BTs in PA6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Energy dispersive X‐ray (EDX) was employed to investigate the elemental mapping and to analyze the blended amounts of PVDF/PCL/KIT‐6 nanocomposites components based on various elements in the samples andto consider changing the KIT‐6 ratio. According to Figure 2, carbon (C) and fluorine (F) as the main elements of the PVDF phase represent peaks at 0.28 and 0.67 keV, respectively 50,51 . The energy peaks of silicon (Si) and oxygen (O) elements are observed at 1.74 and 0.53 keV, respectively, which confirm the presence of KIT‐6 nanoparticles in the matrix; increasing the KIT‐6 content from 1 to 5 wt% intensifies the characteristic Si peaks.…”
Section: Resultsmentioning
confidence: 87%
“…Energy dispersive X‐ray (EDX) was employed to investigate the elemental mapping and to analyze the blended amounts of PVDF/PCL/KIT‐6 nanocomposites components based on various elements in the samples andto consider changing the KIT‐6 ratio. According to Figure 2, carbon (C) and fluorine (F) as the main elements of the PVDF phase represent peaks at 0.28 and 0.67 keV, respectively 50,51 . The energy peaks of silicon (Si) and oxygen (O) elements are observed at 1.74 and 0.53 keV, respectively, which confirm the presence of KIT‐6 nanoparticles in the matrix; increasing the KIT‐6 content from 1 to 5 wt% intensifies the characteristic Si peaks.…”
Section: Resultsmentioning
confidence: 87%
“…The crystallinity calculation formula of polymer matrix nanocomposites is as follows: 52 where Δ H θ m is the melting enthalpy value of 100% crystalline PVDF (∼104.6 J g −1 ) 53 and W f is the weight percentage of nanofillers in the polymer matrix. The calculated results are summarized in Table S3 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Moreover, compared to PVDF, polyvinylidene fluoridehexafluoropropylene (PHP) shows lower dielectric loss and higher breakdown strength. 7 Incorporating various ceramic 8 or conductive 9,10 nanofillers have been extensively studied in the literature in order to improve the relative amount of β phase. Barium titanate (BT) ceramic nanofillers with high dielectric constant improve the dielectric properties of the polymeric matrix [11][12][13][14][15] ; however, it is shown that by refining nanofiller size to nanometer scale, its dielectric permittivity drops down due to transition from tetragonal to cubic structure, 16 thus, higher amounts of BT is required to achieve the desirable improvement which negatively affects the dispersion quality, flexibility and mechanical performance of the composite.…”
mentioning
confidence: 99%